Bony traits and genetics drive intraspecific variation in vertebrate elemental composition. (11th July 2017) - Durston, Daniel J.; El‐Sabaawi, Rana W.
Abstract: Interspecific variation in elemental composition is well known and often leads to predictable differences in ecosystem interactions, but little is known about the extent, causes and importance of intraspecific variation in elemental composition. If intraspecific variation is substantial and has a genetic basis, it may underlie an important mechanism of evolutionary interplay with ecology as individuals compensate for evolutionary changes in elemental demand. To investigate the extent and causes of intraspecific elemental variation in vertebrates, we sampled evolutionary model species Gasterosteus aculeatus (Threespine Stickleback) from 12 locations in British Columbia, Canada. Fish were phenotyped, genotyped for Eda alleles underlying lateral plate variation and assayed for elemental content (C, N, P). We found stickleback vary widely in elemental composition (2.2%–6.5% P; 3.0–9.4: 1 N:P). Phenotypic models explained the majority of this variation using bony armour traits (pelvis length, lateral plate count), bone mineralization, body size and condition. Subsequent genetic models found allelic variation at Eda generates a 7%–14% change in whole organism N:P. As Eda allele frequencies are commonly changed through strong natural selection in freshwater habitats, we infer that stickleback elemental composition can evolve rapidly. Further, as genetics are known to drive variation in many of the other influential traits, we conclude that genetic variation constitutes a major source of variation in the elemental composition of Gasterosteus aculeatus . As such, we find that elemental composition has a large evolutionary potential which may underlie important evo‐eco interactions. A plain language summary is available for this article. Abstract : Plain Language Summary